Penanaman Perilaku Terpuji melalui Ekstrakurikuler Kerohanian di SMA Negeri 5 Karawang - Sarah Sarah; Akil Akil; Jaenal Abidin (ISLAMIKA, 2023)
Basically, the inculcation of commendable behavior is limited to doing good to others, but more than that, researchers describe commendable behavior through spiritual extracurricular activities that take place in public high schools at SMAN 5 Karawang. Which aims to obtain an overview of program activities that have been running for a long time in schools and are character building programs for students. So that making character behavior and getting used to being able to practice their duties and responsibilities as students at school certainly leads to goodness and can be useful in the community in the environment where they are. The method used in this study is a qualitative method with a case study approach, with data collection methods, by way of observation, interviews, and documentation. The results obtained in this study are that students at SMAN 5 Karawang have religious character and character, are polite, maintain the good name of the school, and obey the rules with a culture of inculcating commendable behavior in extracurricular spiritual activities at schools that are carried out every week and become a routine activity at the end of the lesson with religious discussion studies, and social services in commemoration of Islamic holidays such as the Prophet's birthday, Isra'Miraj, and compensation for orphans. That is what will be able to change the character and behavior of students for provision in society. So that he becomes a useful person for himself and others.